EFEKTIVITAS CAMPURAN PROTOKSIN BACILLUS THURINGIENSIS SUBSP. AIZAWAI DAN KONIDIA BEAUVERIA BASSIANA TERHADAP ULAT GRAYAK SPODOPTERA LITURA F. - -, Eka Sukmawati (Fakultas Sains dan Teknologi UIN ALauddin, 2014)
Armyworm or (Lepidoptera:Noctuidae) is one of main pest in plant crop. This pest might cause damage on the leaves and stems and reduce of crop production. Bacillus thuringiensis subsp. aizawai and Beauveria bassiana have been known as biocontrol agent to this pest. This research was aimed to observe the production time of B. thuringiensis subsp. aizawai toxin, measure the effect of toxin against Be. bassianaconidia, to test the activity of their mixture against S. litura. B. thuringiensis subsp. aizawai was grown on specific medium for B. thuringiensis. Toxin production of the isolate was measured every 4 hours up to 48 hours incubation. Be. bassianawas grown on the white rice medium and its conidia was grown on the Potato Dextrose Agar medium. containing toxin. The activity test was done by spraying them to S. litura larvae. The stasionary phase of B. thuringiensis was obtained at 16 hours incubation and the maximal toxin production at 48 hours.. The highest mortality caused the mixture of toxin thuringiensis and conidia Be. bassiana was 96,7%.Key words: Bacillus thuringiensis subsp. aizawai, Beauveria bassiana, toxin, mortality,Spodoptera litura